Oligometastatic gastric cancer: An emerging clinical entity with distinct therapeutic implications. Issue 8 (August 2019) - Salati, Massimiliano; Valeri, Nicola; Spallanzani, Andrea; Braconi, Chiara; Cascinu, Stefano
Abstract: Gastric cancer (GC) remains responsible for a high burden worldwide being the third leading cause of cancer-related mortality. Most of patients present at an advanced stage at diagnosis and are thus candidates to standard chemotherapy resulting in median survival of less than 1 year. Oligometastatic gastric cancer is an increasingly recognized clinical entity characterized by limited metastatic spread that has been showing to benefit from aggressive multimodality strategies encompassing chemotherapy and surgery. The ongoing RENAISSANCE/AIO-FLOT5 (NCT02578368) phase III trial is aimed at evaluating if perioperative chemotherapy with FLOT in combination with surgical resection of the primary tumour and metastases could become the new standard of care for oligometastatic GC. In the meantime, in addition to currently available clinical parameters, the emerging predictive/prognostic role of biomarkers such mismatch repair deficiency/microsatellite instability high status needs to be specifically addressed also in this subgroup of GC to assist in patient selection.